Fotobiomodulação dos LEDs vermelho e verde no processo de reparo em queimaduras de terceiro grau - Simões, Thamyres Maria Silva (2018)
Burns are a global public health problem because of their frequency and their severity. Early intervention in the cicatricial process of burns, especially those of third degree, is fundamental to reduce the severity of the lesions, as well as the complications and physiological compromises that come from them. Among the complementary therapies that have been studied with the objective of accelerating the healing process of these wounds, is the use of Light Emitting Diode (LED). This study aimed to evaluate the photobiomodulation of the red and green LEDs in the third degree burn repair process, through clinical, morphological and immunohistochemical parameters. Sixty male Wistar rats, aged 60-90 days, weighing between 200 and 250 grams, were randomly divided into three groups: control (CTR) (n=20), red LED (RED) (n=20) and GREEN LED (GREEN) (n=20), with subgroups (n=5) for each time of euthanasia (7, 14, 21 and 28 days). The applications of the red LED (λ=520±30nm, 180 mW, 2 60 J/cm per point, 30 seconds) were performed on a daily basis (λ= 630nm±10nm, 300mW, 9J / cm per point, 30 seconds) (total: 36 J / cm2 in VERM and 240 J / cm2 in GREEN), with the exception of the day of euthanasia. After the euthanasia of the animals, the evaluation of 2 the wound retraction index (WRI) was performed. Under light microscopy, histological sections stained with hematoxylin and eosin were evaluated for the surface to be reepithelialized and the angiogenic index (AI) (x400), through the Image J program (version 1.50i). In the immunohistochemical analysis, the anti-α-SMA antibody was used to identify, in the most superficial areas of the connective tissue, the largest amounts of myofibroblasts. The red LED, at 14 and 21 days, induced better reepithelialization and WRI than CTR (p=0.095) and GREEN (p=0.001), the green LED promoted greater angiogenesis in all evaluated periods, and a myofibroblasts superior to the other groups at 21 and 28 days. In conclusion, the red and green LEDs showed beneficial effects on the healing of third degree burns.